Long intergenic noncoding RNA-p21 inhibits apoptosis by decreasing PUMA expression in non-small cell lung cancer. Issue 1 (January 2019) - Yang, Tao; Zhang, Wenjun; Wang, Li; Xiao, Chunyan; Guo, Bingling; Gong, Yi; Liang, Xiping; Huang, Dehong; Li, Qiying; Nan, Yingyu; Xiang, Ying; Shao, Jianghe
Objective: Long noncoding RNAs (lncRNAs) are important mediators in tumor progression. Long intergenic noncoding RNA-p21 (lincRNA-p21) participates in multiple biological processes. This study explored the role of lincRNA-p21 in human non-small cell lung cancer (NSCLC) progression and potential regulatory mechanisms. Methods: LincRNA-p21 expression in NSCLC tissues and cell lines (A549, H1299, H1650, and NCI-H2087) was determined by quantitative real-time PCR. LincRNA-p21 overexpressing and sh-lincRNA-p21 lentiviral were respectively transfected into H1299 and A549 cells. Flow cytometry was used to measure apoptosis. Microarray analysis and RNA pull-down assay were used to predict the target genes of lincRNA-p21. Finally, PUMA siRNA and overexpressing PUMA were transfected into NSCLC cells, and the extent of cell apoptosis was measured. The protein expression levels of the relative genes were confirmed by western blot analysis. Results: LincRNA-p21 was significantly upregulated in NSCLC tissues and cells. The upregulation of lincRNA-p21 considerably inhibited cell apoptosis while the downregulation of lincRNA-p21 showed the opposite effect. PUMA was a direct target gene of lincRNA-p21 and was negatively correlated with lincRNA-p21 in NSCLC specimens. The anti-apoptotic effect of lincRNA-p21 can be effectively attenuated by the upregulation of PUMA. Conclusion: LincRNA-p21 is aberrantly upregulated in NSCLC and inhibits cell apoptosis by decreasing PUMA expression.